"You Can Be an Agent of Change": The Rhetoric of New Age Self-Help in Enlightened. Issue 1 (1st January 2017) - Young, Stephanie L.; Reynolds, D'Arcy J.
Abstract : Extending Cloud's (1998) work on the rhetoric of therapy and Payne's (1989a, 1989b) concept of therapeutic rhetoric, this essay explores discourses of New Age self-help on the HBO television series Enlightened . We argue that New Age self-help rhetoric is a form of therapeutic rhetoric that merges New Age spirituality with the American tradition of self-improvement. We critically examine the show's protagonist, Amy Jellicoe, who engages in New Age self-help rhetoric to enact an "agent of change" identity, and analyze how Enlightened praises and problematizes New Ageism's emphasis on social responsibility. Ultimately, this close textual analysis provides an in-depth look into how New Age tenets are represented in popular culture and the ways in which New Age self-help rhetoric simultaneously resists and reproduces neoliberal individualism within modern society.